Discrepency between Disability and Reported Well-being after Traumatic Brain Injury in Developing Countries - Ishfaque Ahmed Simair, Najam-Us-Saqib Ansari, Abdul Ghafoor Magsi, Zuhaib Ahmed Soomro, Deepak Kumar, Lal Chand Dhingra, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To study the discrepency between disability and reported well-being after traumatic brain injury. Study design: Prospective study. Place and duration of study: Ghulam Muhammad Mahar Medical College Sukkur and S. M. Benazir Bhutto Medical University Larkana from 7th July 2021 to 15th Jun 2022. Methodology: Two hundred and sixty patients suffering from brain injury were enrolled. The patient’s of traumatic brain injury which was represent able through brain computed tomography scan and was reported within 24 hours of the injury and age 10-55 years were included. Scoring tests as Glasgow outcome scale extended and Short Form as well as quality of life scoring was performed in all cases. Functional outcomes were also observed with a follow up of 6 month post traumatic brain injury. There were mild cases of traumatic brain injury as well as moderate to severe cases which for interpretation purposes were divided into two groups. Results: The mean age of these two groups was 36±3.5 and 29±9.7 years and there was more males than females. The satisfaction level for support from hospitalization was seen significantly higher in all cases with no significant variance while it was poorly reported from rehabilitation centers outpatient support to moderate to severe traumatic brain injury cases. The cases with severe disability of upper and lower regions have a very poor functional outcome in cases with moderate to severe traumatic brain injury. The score for quality of life and mental physical well-being was not in normal ranges for moderate to severe cases of traumatic brain injury. Conclusion: There are discrepancies in patients reporting of well-being and disability outcomes in traumatic brain injury cases. Keywords: Discrepancy; Disability; Traumatic Brain Injury